2014
DOI: 10.1155/2014/248198
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Knowledge, Attitudes, and Behaviors in Collegiate Athletes

Abstract: Outdoor athletes represent an important group at risk for skin cancer because they are routinely exposed to high levels of ultraviolet radiation. The purpose of this study was to assess current skin cancer knowledge, attitudes, and behaviors among collegiate athletes. A modified version of the Melanoma Risk Behavior Survey was completed by 343 athletes attending a Southern University in the USA, generating an 87% response rate. Survey results demonstrated that the majority of the athletes do not limit their su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
(28 reference statements)
4
29
0
3
Order By: Relevance
“…When comparing the data with the demographics, it was found that the participant's age did not influence the sun protective behaviors, knowledge, or attitude. Those with a darker pigmentation knew less about skin cancer risk factors than Caucasians (Hobbs et al, 2014). It was found that race did not influence sun protective behaviors or attitude toward skin cancer.…”
Section: Using Sunscreenmentioning
confidence: 89%
See 4 more Smart Citations
“…When comparing the data with the demographics, it was found that the participant's age did not influence the sun protective behaviors, knowledge, or attitude. Those with a darker pigmentation knew less about skin cancer risk factors than Caucasians (Hobbs et al, 2014). It was found that race did not influence sun protective behaviors or attitude toward skin cancer.…”
Section: Using Sunscreenmentioning
confidence: 89%
“…This study compared the demographic information with the level of knowledge and level of protective behaviors. Given that the most modifiable risk factor for skin cancer is controlling the amount of exposure to ultraviolet radiation (UVR), effective methods for lowering UVR are as follows: limiting exposure during midday, wearing sunglasses, wearing protective clothing and hats, seeking shade during midday, and wearing sunscreens with SPF 30 or more (Hobbs et al, 2014). Through this study, it was found that most collegiate athletes were not protecting themselves against the sun.…”
Section: Databasementioning
confidence: 96%
See 3 more Smart Citations